(3GdfbhO hGdJehjd GdOhdjs - (3Sj Hhd(B, (3gGdhhOs; (3QhfGdO eGcOhfGdO(B, s ((3GdQjGV(B:s (3OGQ GdeQjN ddTQ(B,s, 2007)
(3HYV GdeaGgje GdCSGSjI ddJehjd GdOhdj, CSYGQ GdUQa GdMGVQI hGdBLdI, GdONd hejRGf GdeOahYGJ, GdLhGfH GdEbJUGOjI GdcdjI aj GbJUGO eaJhM, JfSjb GdSjGSGJ GdEbJUGOjI Ydi eSJhi GdOhdj, JYGOd GdbhI GdTQGFjI, GdfXQjI hGdHQgGf GdYedj, GdefgL GdfbOj dejRGf GdeOahYGJ, GdfXQI GdfbOjI dJMOjO SYQ GdUQa, GdfehPL GdfbOj, JWHjbGJ CNQi Yf GdUOeGJ GdMbjbjI hJbdH fXGe SYQ GdUQa, efgL ejRGf GdeMaXI GdeGdjI dJMOjO GdSYQ GdUQa, GSYGQ GdUQa GdMGVQI hGdBLdI haQVjIcaGAI GdCShGb, GdJaSjQGJ GdNGUI HGdJhbYGJ dQaV aQVjI caGAI GdCShGb,aQVjI GdCNHGQ, CReGJ GdYedI hgLeGJ GdeVGQHI, GdefGWb GdeSJgOaI dSYQ GdUQa hGdJbhje ZjQ GdfXja, bGYOI GdPgH GdOhdjI, bGYOI GdOhdGQ, GdEJMGOGJ GdfbOjI, GdJOabGJ GdOhdjI dQCS GdeGd, GdOhd GdBNPI aj Gdfeh, ehGAeI ejRGf GdeOahYGJ hUfOhb GdfbO GdOhdj, JfXje YedjI GdJMQjQ GdEbJUGOj aj GdOhd GdBNPI aj Gdfeh, CSYGQ GdUQa hGbJUGOjGJ Ohd GdJMhd GdEbJUGOj, GdOjhf GdYGdejI, GdEUdGM GdfbOj GdOhdjs
Keywords: (3GdJehjd GdOhdjs; (3GdfbhOs